Usefulness of japanese bunching onion (Allium fistulosum L.) for forcing in greenhouse - Maria Tendaj; Barbara Mysiak (Acta Agrobotanica, 2012)
The purpose of this work was the evaluation of yielding and the content of some chemical ingredients of Japanese bunching onion yield obtained from forcing in greenhouse conditions. Plants used for forcing were from field cultivation and had the pseudostem trimmed in the autumn of each year (2002, 2003 and 2004) at the height of 2-4 and 8-10 cm. In the spring of the following year (2003, 2004 and 2005) from the middle of March, the plants were forced in a heated greenhouse (temperature 16-20°C) and an unheated one (temperature 6-12 °C). The whole yield was evaluated when the plants reached the market size for bunching. The weight and height were determined in the plants, as well as the number of laterals and leaves in clusters. In green shoots and the pseudostem, the content of dry weight, total and reducing sugars, L-ascorbic acid, flavonoids and phenolic acids were determined. Very high yield of plants useful for bunching was obtained (average 13.7 kg·m-2 of area). The plants with a longer pseudostem before forcing yielded better. The conditions of forcing did not have a significant influence on the size of the obtained yield, but the content of L-ascorbic acid and flavonoids was much higher (especially in green shoots) in the plants from forcing in the unheated greenhouse. Lower temperature at the time of forcing was favorable to higher reducing sugar content, especially in the pseudostem. Japanese bunching onion turned out to be useful for forcing for harvest in bunching form.